Policy, design, and way of life in resettlement projects: The case of Ashrayan, Bangladesh. (July 2022) - Parvin, Afroza; Hakim, Sheikh Serajul; Islam, Md Azharul
Abstract: Bangladesh is home to millions of landless and homeless people internally displaced by extreme weather events like tropical cyclone, flooding, water surge, and riverbank erosion. State-led resettlement projects have resettled about half a million people in the last two decades with a target to resettle nearly a million more in phases. These top-down initiatives are criticised to be more physical outcome-focused and less sensitive to the socio-cultural and physical-spatial dimensions of the resettled people's life. As a result, these people struggle to cope with the 'designed' living environment that is new to their everyday lived experiences. Owing to this discord, a semester-long architectural design-research studio was conducted to develop people-place-specific alternative design schemes focusing on the socio-cultural way of life; socio-spatial way of living and agrarian livelihood of the displaced communities. Drawing on part of the design studio, this research is designed with a three-stage multi-disciplinary research methodology that includes: critical appraisal of the largest government-led resettlement project ( Ashrayan ); exploring settlement morphology of a Ashrayan project village; and proposing alternative resettlement housing design schemes for the riverbank erosion-displaced people. Based on empirical findings, this research argues that there exists a significant knowledge gap in the policy and design domains regarding the meaning and process of resettlement in general, and people's way of life, living and livelihood in particular. Outcomes of this research contributes people-place-sensitive strategic guidelines toward filling this gap in an informed manner. Highlights: World's largest resettlement project has been initiated in Bangladesh with a pro-people political will. Resettled communities struggle to negotiate their way of life and livelihood in the resultant Barrack housing. The One-size-fits-all physical-spatial design struggles to mingle with the rural settlement pattern. Need to re-think the Ashrayan policy, process and design approaches.